FEEDSTOCKS USED FOR PRODUCTION OF 2ND AND 3RD GENERATION BIOETHANOL - REVIEW - Vasile-Florin URSACHI (Stefan cel Mare University of Suceava, 2020)
Global biofuel production has increased significantly over the last decade, but first-generation biofuels have been identified as a major concern, especially their sustainability as they are produced from food crops (such as cereals, sugar cane and vegetable oils). Depending on the feedstocks and cultivation technique, the production of second and third generation biofuels has the potential to provide benefits, such as the recovery of residues and unusable land. Therefore, second and third generation biofuels are indicated to meet the increasing demand for energy and contribute considerably to the development of rural areas and the increasing of bioeconomy. This short review shows that there may be different types of feedstocks (agricultural residues, forest residues, energy crops and algae) which can be used for the production of 2nd and 3rdgeneration bioethanol without affecting food security.